Penerapan Algoritma K-Means Pada Penjualan Frozen Food Pada UD Soise Sosis Pematangsiantar - Nasution, Siti Andry Yani; Poningsih, Poningsih; Okprana, Harly (STMIK Budi Darma, 2021)
The research objective is the application of the K-Means algorithm in Frozen Food sales, to classify the number of Frozen Food sales in each month, to take what month the highest and lowest sales data. The method used is the K-Means algorithm and is accompanied by a Rapid Miner in processing the data. Data sources obtained from observations, interview and document to shop owners and coworkers. There are several types of Frozen Food and sales data from April to November 2019. Where the results of the study can provide information to business owners, what Frozen Food should be increased in production so that business owners can increase their Frozen Food sales.